(untitled) (Jurnal Teknologi (Sciences & Engineering), 2015)
This paper aims to explore the history and development of eight types of reaction water turbines, namely Hero’s turbine, Barker’s mill, Pupil’s turbine, Whitlaw’s mill, Quek’s turbine, the cross pipe turbine, the split reaction turbine and the Z-Blade turbine. These water turbines are discussed in terms of the complexity of the designs, the manufacturing processes involved, and the applications. It has been observed that even though most reaction type water turbines, except for the split reaction turbine and Z-blade turbine, have undergone different levels of design-related modifications and manufacturing processes, they are considered as being unsuitable for low-head and low-flow water resources in pico-hydro systems.